syn-2,4-Bis(4-methoxybenzylidene)-trans-1,3-dithexyl-2,4-diaza-1,3-diboracyclobutane - Lesley, M. J. G.; Pineau, M. R.; Nelson, D. M.; Crundwell, Guy (Acta Crystallographica Section E-structure Reports Online, 2007)
In the crystal structure of the title compound, C28H44B2N2O2, the square-planar B2N2 ring is slightly puckered. One of the thexyl groups exhibits disorder over two positions. The site occupancies for the disordered thexyl groups refined to 0.611 (4) and 0.389 (4). © 2007 International Union of Crystallography.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00366 tex.type: [object Object]
Keywords: dept.che